The sensitivity of brewing micro-organisms to silver - Strecker, P.G. (2015)
With respect to microbiological food safety, beer is thought to be very safe. This is due to the inability of pathogenic organisms to survive in the harsh environment that beer presents, due to low pH, alcohol content and hop acids. However, there are some organisms which have adapted to brewery conditions and can cause off-flavours, hazes or low ethanol yield. The effects of spoilage and subsequent product recall can result in massive economic losses for brewing companies affected. Silver nano particle coatings for pipes and vessels have been suggested as a means of eliminating or reducing contaminants in the brewery. In this study the sensitivity of several brewery contaminants to silver has been investigated. Pichia membranaefaciens, Brettanomyces anomalous, Candida krusei, Hansenula saturnus, Kloeckera apiculata, Rhodotorula mucilaginosa, Saccharomyces ellipsoids var. diastaticus, Lactobacillus brevis, Pediococcus damnosus, were all tested against a range of silver nitrate concentrations (0-1 mM) in YPD, wort and beer. It was found that sensitivity to silver varied between organisms, but no tolerance exceeded 0.55 mM. It was also found that for the majority of organisms, tolerance to silver decreased under simulated brewery conditions i.e. wort, beer and microaerophillic conditions. In the investigation of potential silver tolerance mechanisms, gene microarrays of Saccharomyces ellipsoids var. diastaticus in wort and beer in the presence and absence of silver found that genes most up-regulated during silver stress were those with transmembrane transporter functions. Silver tolerance testing with gene deletion strains of selected potential silver tolerance genes demonstrated reduced silver tolerance for the deletion strains of the HIS1, COX17 and CUP1 genes. All three of these have known functions in copper tolerance. The data collected in this study would suggest that silver (particularily in nanoparticle form) is an effective means of microbial brewery contamination control especially under brewery conditions. However, further study is needed into the effect of silver antimicrobial surfaces on brewery microbial contaminants, silver concentrations needed in antimicrobial surfaces and silver leaching etc.